Analisis Kompetensi Spiritual Yusuf Berdasarkan Kejadian 37-50 pada Siswa Siswi SD-SMP Swasta Advent Lumbangambiri - Simanjuntak, Kornel; Pane, Exson Eduaman (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
The purpose of this study is to better understand how high the level of understanding of students and students of SD and SMP Swasta Advent Lumbangambiri about Joseph's spirituality based on the Book of Genesis Articles 37-50. The research method used quantitative survey research. The results showed that there is a relationship between kindness, responsibility, integrity and competence to hope in God towards the study of Joseph's spiritual competence based on the Book of Genesis Chapter 37-50 on the students of SD-SMP Private Adventist Lumbangambiri, Central Dairi District. Overall, respondents almost have a mediocre or moderate understanding of Joseph's spirituality based on the Book of Genesis chapters 37-50 for students at SD-SMP Swasta Advent Lumbangambiri Central Dairi District which is 3.84-5.00.